Multimeter as Alternative Measurement System in the Potentiometric Titrations - Pérez-Saavedra, José de Jesús (2015)
In this paper, we experimentally demonstrated by the statistical test Student t, the usual potentiometric titrations in analytical chemistry (acid-base, redox, complexometric and halides) can be performed using as indicator system to valuation a multimeter instead of the potentiometer. Enabling this, teaching laboratories, can be equipped at low cost with multimeters rather than potentiometers.